2013
DOI: 10.1186/1471-2164-14-670
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of the PacBio RS platform for sequencing and de novo assembly of a chloroplast genome

Abstract: BackgroundSecond generation sequencing has permitted detailed sequence characterisation at the whole genome level of a growing number of non-model organisms, but the data produced have short read-lengths and biased genome coverage leading to fragmented genome assemblies. The PacBio RS long-read sequencing platform offers the promise of increased read length and unbiased genome coverage and thus the potential to produce genome sequence data of a finished quality containing fewer gaps and longer contigs. However… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
125
1
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
3
3

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(137 citation statements)
references
References 32 publications
7
125
1
3
Order By: Relevance
“…Results indicate that the coverage in WT plants has a similar pattern to those previously reported in the literature for plastid genomes (Wu et al 2012;Ferrarini et al 2013) and to that of all single and double mutant lines used in this study (Supplemental Fig. S4).…”
Section: U-turn-like Rearrangements Are Associated With Replication Ssupporting
confidence: 74%
“…Results indicate that the coverage in WT plants has a similar pattern to those previously reported in the literature for plastid genomes (Wu et al 2012;Ferrarini et al 2013) and to that of all single and double mutant lines used in this study (Supplemental Fig. S4).…”
Section: U-turn-like Rearrangements Are Associated With Replication Ssupporting
confidence: 74%
“…Although sizeable error rates (∼13%) have been reported [8], these errors are random, in contrast to context-specific errors (e.g. palindromic sequences or GC rich contents) that are generally observed in other techniques, such that multiple lower-quality base calls can be aligned to derive high-quality (de-novo) sequence data [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…The first report of total plant DNA analysis for chloroplast sequencing (Nock et al 2011) used short Illumina reads (36 bp) and relied on a reference genome for successful assembly. More recent studies based upon longer reads (Ferrarini et al 2013;McPherson et al 2013) have reported more success with de novo assembly.…”
Section: Discussionmentioning
confidence: 99%
“…Various NGS technologies are now available for the rapid sequencing of whole genomes (Ferrarini et al 2013;Rothberg et al 2011;Shendure & Ji 2008). The choice of selecting one or more NGS technologies depends on the yield of data required, read length required, cost per data point and accuracy of the sequence data (Quail et al 2012).…”
Section: Discussionmentioning
confidence: 99%